Plasmapheresis and Multidisciplinary Intensive Care Management for Guillain-Barré Syndrome with Prolonged Mechanical Ventilation: A Case Report - Indrawan, Khadafi; Manggala, Sidharta Kusuma (Writing Center IMERI FMUI, 2024)
Guillain-Barré syndrome (GBS) is a rare, acute autoimmune peripheral neuropathy often triggered by infections. It leads to rapid-onset muscle weakness and, in severe cases, respiratory failure requiring mechanical ventilation. Plasmapheresis is recommended to reduce circulating autoantibodies that damage peripheral nerves. Guidelines suggest that early initiation of plasmapheresis may improve clinical outcomes, especially in patients with significant motor weakness. A 41-year-old female was referred to the emergency room with progressive ascending bilateral limb weakness, sensory deficits, and urinary incontinence. Symptoms emerged 26 days prior and treatments from previous hospitals were ineffective. Physical examination revealed cranial nerve involvement, proprioceptive disturbance, and reduced deep tendon reflexes. Laboratory tests showed leukocytosis, thrombocytosis, hypoalbuminemia, electrolyte imbalance, and elevated D-dimer. Cerebrospinal fluid analysis was normal. The patient was diagnosed with GBS, intubated by day six post-admission due to respiratory failure and tracheotomized by day eight. The patient was admitted to the intensive care unit. Plasmapheresis, initiated on day 17, improved motor strength after three sessions spaced over 10 days. However, delayed intervals between sessions and limited access potentially impeded the recovery process. Despite improvements, the patient remained ventilator-dependent and require multidisciplinary interventions. Inhalation therapy, enteral feeding, physical rehabilitation, and psychiatric interventions were administered. The family was informed of potential long-term ventilator dependency and home care preparation. This case underscores the importance of timely plasmapheresis and coordinated, multidisciplinary ICU management in severe GBS, encompassing neurological treatment, respiratory care, nutrition management, physical rehabilitation, and psychological support for the patient and their caregivers.